2016
DOI: 10.5433/1679-0359.2016v37n6p4221
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and safety of meat from cattle feedlot finished with salinomycin in the diet

Abstract: This study assessed production performance, carcass characteristics, serum parameters, residue depletion of meat, and economic performance during the finishing period of steers in feedlots using salinomycin in their diet. A total of 32 steers were finished in a feedlot on a diet comprising corn silage and concentrate (50:50), with or without added salinomycin (120 mg per animal day -1 ). Study design was completely randomized, with eight repetitions. Results indicated that the use of salinomycin increased both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…The lack of effects of antibiotic growth promoters on digestibility (except for digestibility of NDF) was also observed in other studies with the inclusion of ionophores (Mcallister et al, 1994;Neumann et al, 2016) or virginiamycin (Salinas-Chavira et al, 2009). However, ionophores can increase dietary digestibility by increasing the DM retention time in the rumen because of lower voluntary intake, stimulating rumination, and improving the ruminal environment (Ellis et al, 1983).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The lack of effects of antibiotic growth promoters on digestibility (except for digestibility of NDF) was also observed in other studies with the inclusion of ionophores (Mcallister et al, 1994;Neumann et al, 2016) or virginiamycin (Salinas-Chavira et al, 2009). However, ionophores can increase dietary digestibility by increasing the DM retention time in the rumen because of lower voluntary intake, stimulating rumination, and improving the ruminal environment (Ellis et al, 1983).…”
Section: Discussionmentioning
confidence: 56%
“…The supply of antibiotic growth promoters did not affect the intake DM by steers. Previous studies also showed no effect of LASA (Golder and Lean, 2016), SALI (Neumann et al, 2016) and VIRG (Montano et al, 2015) on intake DM. However, others have reported that ionophores can reduce intake when used in diets with a high proportion of concentrate (Vargas et al, 2001).…”
Section: Discussionmentioning
confidence: 82%
“…Variations in serum parameters during the confinement period are related to age. In a study evaluating these same serum parameters and with animals of the same age, changes were also observed during the confinement period, however the literature reports that the levels of TP, albumin, fibrinogen, AST, GGT are directly influenced by the animal age, because until puberty, there are changes in their metabolism and body composition, such as changes in the rate of bone, muscle and fat tissue deposition (21,22) .…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, redução do CMS de 4 a 6% e melhoria da EA de 6 a 14,8% foram observados em bovinos alimentados com dietas ricas em concentrado contendo níveis de 11 a 50 mg/kg MS de suplementação de salinomicina (Wagner, 1984;Merchen and Berger, 1985;Zinn, 1986a). No entanto, alguns estudos não demonstraram alteração do CMS de bovinos confinados com adição de 11 e 12,6 mg/kg MS de salinomicina (Zinn, 1986b;Neumann et al, 2016) ou 10,6 mg/kg MS de narasina (Gobato et al, 2017). Todavia, vale ressaltar que a narasina e a salinomicina demonstraram ser eficazes na melhora da EA em uma dosagem menor do que a lasalocida e a monensina (Bergen and Bates, 1984).…”
Section: Ionóforosunclassified